In vitro antiviral activity of dieckol and phlorofucofuroeckol-A isolated from edible brown alga Eisenia bicyclis against murine norovirus - Eom, Sung-Hwan; Moon, Sun-Young; Lee, Dae-Sung; Kim, Hyo-Jung; Park, Kunbawui; Lee, Eun-Woo; Kim, Tae Hoon; Chung, Yong-Hyun; Lee, Myung-Suk; Kim, Young-Mog (Algae (Korean Phycological Society), 2015)
This research was conducted to develop effective and safe marine-derived antiviral compounds against norovirus. The ethyl acetate (EtOAc)-extract from Eisenia bicyclis exhibited strong antiviral activity against murine norovirus (MNV) as a norovirus surrogate. Among the phlorotannins from E. bicyclis, dieckol (DE) and phlorofucofuroeckol-A (PFF) were known to possess the strongest antibacterial activity. In this study, DE and PFF were evaluated for antiviral activity against MNV. DE and PFF exhibited strong anti-MNV activity with 50% effective concentration of 0.9 μM. However, PFF exhibited more effective antiviral activity against MNV with higher selective index (668.87) than that of DE (550.60), due to its lower cell toxicity against RAW 264.7. This is the first report on the anti-MNV activity of phlorotannins from seaweed. The results obtained in this study suggest that the phlorotannins could be used as a potential source of natural antiviral agents.